The level of sexual education - problem of middle school students - Marzec, Alicja Małgorzata; Orłowska, Izabela; Pluta, Agnieszka (Journal of Education, Health and Sport, 2017)
Introduction. The problem of sexual education of school youth is described as difficult, permanently current and open. Low, insufficient level of preparedness for sexual initiation manifests itself in the statistics of early motherhood and early parenthood. Assigned to the school as an environment education and teaching, the role of education is not fulfilling in terms of sexual education. Students expect their parents more involvement in sexual education. Aim. The aim of this study is to examine the current level of interest of middle school students in sexual education and to determine their expectations in this range. Material and methods. The study was carried out by the method of diagnostic survey, using the questionnaire in the study of our own. The research included students of 1st and 2nd class of middle school (n = 50, 31 boys, 19 girls), aged 13-14 years. Results. In the examined group the interest in sexual education expressed 78%, but only 14 % of the respondents talked with their parents about it, and 20% do not want such talks, 62% talked about it with their mothers, 46% the side who initiates the conversation was a student. Dissatisfied, disappointed with the quality of classes the education for family life was 42% of middle school students. Conclusions. Middle school students showed interest in sexual education at school. The range of themes which interest the youth is consistent with the thematic scope of the program of subject the education for family life. Middle school students express dissatisfaction with the quality of sexual education classes and would like a greater participation of parents in sex education.